The dynamic response of seabed anchored floating tunnels under seismic excitation. - Fogazzi, P.
In this paper a procedure for analysing the seismic response of seabed anchored floating tunnels is presented. The first step of the research was the development of an'ad hoc' finite element for modelling the behaviour of anchor elements, with particular reference to the problem of transverse oscillations under time varying axial loads. The element was subsequently inserted ina step by step procedure for the numerical analysis of non-linear response to multiple support seismic input; the procedure encompasses simplified modelling of fluid structure and soil structure interaction effects. An example of an application is given concerning two 4680 m long floating tunnels with different seabed profiles.
Keywords: Submerged structures; Non-linear structural dynamics; Multiple support seismic excitation